2014
DOI: 10.1103/physrevb.90.125430
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confinement and band offsets in amorphous silicon quantum wells

Abstract: Quantum wells (QWs) are nanostructures consisting of alternating layers of a low and high band-gap semiconductor. The band gap of QWs can be tuned by changing the thickness of the low band-gap layer, due to quantum confinement effects. Although this principle is well established for crystalline materials, there is still controversy for QWs fabricated from amorphous materials: How strong are the confinement effects in amorphous QWs, where, because of the disorder, the carriers are localized to start with? We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…We note that we expect only weak quantum confinement and charge localization effects in the amorphous part, since the charge carriers in bulk a-Si:H are localized to begin with. 29 In order to circumvent the problem with quantum confinement in the c-Si part we followed a different approach. We calculated the band structure of c-Si with 2 atoms in the unit cell and obtained a band gap of 1.14 eV (HSE06).…”
Section: Electronic Structure Of the Interfacementioning
confidence: 99%
“…We note that we expect only weak quantum confinement and charge localization effects in the amorphous part, since the charge carriers in bulk a-Si:H are localized to begin with. 29 In order to circumvent the problem with quantum confinement in the c-Si part we followed a different approach. We calculated the band structure of c-Si with 2 atoms in the unit cell and obtained a band gap of 1.14 eV (HSE06).…”
Section: Electronic Structure Of the Interfacementioning
confidence: 99%
“…For example, the quantum well is a significant material with a discrete energy level. Its band gaps always decrease as the quantum well thickness increases (Jarolimek et al, 2014). This research indicates that the size of the semiconductor is crucial in adjusting the electronic properties.…”
Section: Introductionmentioning
confidence: 77%
“…As the size increases, and the band gap decreases (Wu et al, 2005;Wilcoxon et al, 1997). Researchers have used quantum confinement to adjust the band structures of semiconductor materials (Arutyunov et al, 2018;Peng et al, 2018; OPEN ACCESS EDITED BY Haichang Zhang, Qingdao University of Science and Technology, China Chang et al, 2012;Jarolimek et al, 2014). For example, the quantum well is a significant material with a discrete energy level.…”
Section: Introductionmentioning
confidence: 99%
“…Surveying broadly studied DFT hybrid functional on various silicon related materials, we confirmed that the tendency of band gap estimation by the PBE level has been in parallel to that by the hybrid functional. [40][41][42] We expect in our model study that the PBE level discussion for three relevant configurations as shown in Fig. 5 would not be far from the hybrid functional one.…”
Section: Density Of States and Energy Gaps For Model Configurationsmentioning
confidence: 99%